Application of improved equivalent modeling method in dynamic performance analysis of printed circuit boards - Jianbo Wang; Leiyao Liu; Haiping Liu; Xiaokun Zhang; Yuhui Bai; Jiaxi Jin; Zhaobo Chen (Results in Engineering, 2025)
The structural dynamic performance of printed circuit boards (PCB) directly affects the reliability and stability of onboard electronic equipment in vibration and shock environments. Hence, studying and analyzing the structural dynamic performance of PCBs holds significant importance. In order to address the issue of low computational efficiency resulting from the necessity of establishing a large mesh of elements and considering various boundary and contact conditions in traditional finite element methods, this study comprehensively considers the complexity and variability of PCB structures, encompassing factors such as differing layers, materials, sizes, and irregular component distributions. Through this approach, a more accurate dynamic model of the PCB is achieved. The established PCB model primarily includes equivalent processing of the PCB substrate and onboard components, along with equivalent calculations of various boundary conditions. Ultimately, an equivalent PCB dynamic model is obtained, possessing similar or approximate mass distribution and natural frequency characteristics as the actual PCB, with a deviation less than 6.63 %.